Pengeluaran Pemerintah dan Pertumbuhan Ekonomi di Indonesia : Analisis Panel Seemingly Unrelated Regression - Kharisma, Bayu; Pratikto, Adji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.01.TAHUN 2019DO - 10.24843/EEB.2019.v08.i01.p01, 2018)
The paper aims to examine how the growth impact of government spending in Indonesia, with a focus on several expenditure sectors, namely defense, education, health, agriculture, transport and communications, and manufacturing sectors. Based on the 17 sectors studied, only 6 sectors significantly influence economic growth, namely industrial sector, agriculture and irrigation sector, transportation and transportation sector, environment and spatial sector, political sector and mass media lighting, and security of order. Meanwhile, of the six sectors, only the security sector of order has a positive effect on economic growth, while the other five sectors negatively affect economic growth. If not paid attention to the level of significance, almost all sectors of development expenditure have a negative impact on economic growth, only 5 sectors that have a positive influence that is the labor sector, education sector, national culture, trust in God YME, youth and sports, housing and residential sector , the science and technology sector, as well as the security and order sectors. However, only the security sector of order has a significant effect, while the other four sectors have no significant effect. This result differs from previously conclusions, where their overall conclusion of the government development spending sector has a significant effect, the effect being positive. However, the same conclusions are generated for the security and order sectors, where the results are positive and significant.